Pengaruh Pendekatan Diferensiasi dalam Inquiry-based Learning terhadap Kemampuan Penguasaan Konsep Siswa SMA pada Topik Usaha dan Energi - Winny Liliawati; Hera Novia; Devi Ayu Nur'aini (Postgraduate, University of Mataram, 2023)
This study aims to investigate the effect of the differentiated approach on high school students' conceptual understanding of the work and energy topic. The research method used is a quantitative method. Two classes of 10th graders in one of the Senior High Schools in the Tangerang districts were chosen to be research participants with cluster random sampling. Data collection was done with learning style questionnaire and conceptual understanding item with a reliability 0.73. The experimental class applied Inquiry-based Learning with differentiation, while the control class applied Inquiry-based Learning without differentiation. The results of the different tests of students' conceptual understanding after learning showed a significant difference in the understanding of students' concepts in the two classes. The effect size score showed a large effect of a differentiated approach on students' conceptual understanding. The analysis of the level of students' conceptual understanding for each subtopic showed the Law of Conservation of Mechanical Energy having the most students at irresponsiveness level, while the subtopics with the highest number of students at the understanding level was the work subtopic. The percentage of students who studied with a differentiated approach at the highest understanding level is more than students without a differentiated approach in all subtopics. Although the application of the differentiated approach had obstacles in online learning, the differentiated approach applied in Inquiry based Learning has a positive impact in facilitating the diversity of student learning styles.